Budidaya Jamur Tiram sebagai Peluang Usaha Baru di Desa Batu Kumbung - Torikul Azis; Joko Sumarsono; Agus Pratomi Mulyo; Anggun Oktaviani; Rani Bahiratun Azizah; Sofiatunnufus Sofiatunnufus; Ayu Dahlia; Sapena Farida; Ananda Rizantia Nurmalia; Melia Safirani Fitri (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
The University of Mataram carries out Community Service (KKN) activities, and the main work program carried out is oyster mushroom cultivation. This work program aims to empower the community by cultivating oyster mushrooms and processing oyster mushrooms to improve the welfare of Pengonong hamlet, Batu Kumbung Village Lingsar District. The methods are submitting material on oyster mushroom cultivation and its processing, discussing various problems related to oyster mushroom cultivation and their solutions, business management and product marketing, simulation, and evaluation. This activity was carried out from December to February 2022. The implementation of this activity involved University of Mataram Community Service students as facilitators. The evaluation results of this activity indicate that the cultivation of oyster mushrooms and their products positively impacts the local community. The community is very responsive to this activity. The prospect of the oyster mushroom market still has considerable opportunities. The output of this activity is to produce several baglogs of oyster mushrooms and produce reference journals on oyster mushroom cultivation